APPLICATION OF SHOCK WAVE THERAPY IN THE TREATMENT OF CALCIFIC TENDINOPATHIES - Topalović, Ivana; Nešić, Dejan (Medicinski podmladak, 2022)
Tendons are the soft tissue that connects muscles to bones. They are made of collagen and elastin, they are strong and solid and have no possibility of contraction. Their strength helps us to move. Recovery of tendon injuries is long-lasting and can take more than six months. If a tendon is shed during a time injury, calcification occurs at the site of the injury, and the disease is called calcifying tendinopathy.The very existence of calcifications is an indication for treatment with a mechanical shock wave (Shock wave). Mechanical shock waves act in focus or radially. The difference between focused and radial waves is primarily in their physical basis. Focused shock waves differ from radial shock waves in terms of therapeutic depth of penetration into the tissue. The basic biological effect of a mechanical shock wave is stimulating. The energy of the mechanical shock wave acts at the cellular level by stimulating the reduction of inflammation and pain in the tissue. Using Shock wave in the treatment of calcified tendinopathies, a safe method for breaking calcifications was obtained. Shock wave can be applied to using: different frequency, different number of strokes, as well as different strength of strokes in their studies. The choice of parameters for the application depends on whether it is calcified or non-calcified tendinopathy.Indications for use are: painful shoulder, heel spur, plantar fasciitis, tennis elbow, Achilles tendon tendinopathy, jumping knee, patellar tendinitis, myalgia, myogelosis and muscular tendon overstrain syndrome. Contraindications for use are: the existence of prostheses, knees and hips, as well as various orthopedic material, pacemaker, as well as the presence of chronic diseases such as multiple sclerosis, amyotrophic lateral sclerosis or tumors.The application of a mechanical shock wave is new, non-invasive method, easy to apply, always reduces pain and practically without side effects. This method has a special role in the treatment of chronic inflammation of diseased tendons, with or without calcification. The only dilemma in the application of a mechanical shock wave can be in the number of applications as well as the time break between the application of two consecutive mechanical shock waves.
Keywords: tendinopathy, calcification, mechanical shock wave, plantar fasciitis, tennis elbow